Decoloniality as the Future of Africa - Ndlovu-Gatsheni, Sabelo J. (History compass, 2015)
Decoloniality is not only a long-standing political and epistemological movement aimed at liberation of (ex-) colonized peoples from global coloniality but also a way of thinking, knowing, and doing. It is part of marginalized but persistent movements that merged from struggles against the slave trade, imperialism, colonialism, apartheid, neo-colonialism, and underdevelopment as constitutive negative elements of Euro-North American-centric modernity. As an epistemological movement, it has always been overshadowed by hegemonic Euro-North American-centric intellectual thought and social theories. As a political movement, it has consistently been subjected to surveillance of global imperial designs and colonial matrices of power. But today, decoloniality is remerging at a time when the erstwhile hegemonic Euro-North American-centric modernity and its dominant epistemology are experiencing an epistemological break. This epistemic break highlights how Euro-North American-centric modernity has created modern problems of which it has no modern solutions and how theories/knowledges generated from a Euro-North American-centric context have become exhausted if not obstacles to the understanding of contemporary human issues. This essay introduces, defines, and explains the necessity for decoloniality as a liberatory language of the future for Africa.